Morphometric Differences of Vocal Tract Articulators in Different Loudness Conditions in Singing - Echternach, Matthias; Burk, Fabian; Burdumy, Michael; Traser, Louisa; Richter, Bernhard (PloS one, 2016)
Dynamic MRI analysis of phonation has gathered interest in voice and speech physiology. However, there are limited data addressing the extent to which articulation is dependent on loudness. 12 professional singer subjects of different voice classifications were analysed concerning the vocal tract profiles recorded with dynamic real-time MRI with 25fps in different pitch and loudness conditions. The subjects were asked to sing ascending scales on the vowel /a/ in three loudness conditions (comfortable=mf, very soft=pp, very loud=ff, respectively). Furthermore, fundamental frequency and sound pressure level were analysed from the simultaneously recorded optical audio signal after noise cancellation. The data show articulatory differences with respect to changes of both pitch and loudness. Here, lip opening and pharynx width were increased. While the vertical larynx position was rising with pitch it was lower for greater loudness. Especially, the lip opening and pharynx width were more strongly correlated with the sound pressure level than with pitch. For the vowel /a/ loudness has an effect on articulation during singing which should be considered when articulatory vocal tract data are interpreted.